2019
DOI: 10.4103/sjg.sjg_189_18
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy of ledipasvir/sofosbuvir for 8 weeks in non-cirrhotic chronic hepatitis C genotype 4 patients

Abstract: An 8-week regimen of LDV/SOF was well tolerated and efficacious in this treatment-naïve, non-cirrhotic HCV GT4-infected population. This study provides valuable information on a short treatment regimen for HCV GT4 infection in a real-world setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The addition of ribavirin has not been found to improve the efficacy of the combination regimen[158,159]. In a recent real-world study, an 8-wk regimen of ledipasvir + sofosbuvir was found to be well-tolerated and effective in treatment-naïve and noncirrhotic HCV GT4-infected patients ( n = 45) (SVR12: 97.8%)[160]. Studies evaluating the efficacy of sofosbuvir + ledipasvir + ribavirin regimen in HCV GT4-infected liver transplant recipients are limited.…”
Section: Optimizing the Management Of Hcv Infectionmentioning
confidence: 99%
“…The addition of ribavirin has not been found to improve the efficacy of the combination regimen[158,159]. In a recent real-world study, an 8-wk regimen of ledipasvir + sofosbuvir was found to be well-tolerated and effective in treatment-naïve and noncirrhotic HCV GT4-infected patients ( n = 45) (SVR12: 97.8%)[160]. Studies evaluating the efficacy of sofosbuvir + ledipasvir + ribavirin regimen in HCV GT4-infected liver transplant recipients are limited.…”
Section: Optimizing the Management Of Hcv Infectionmentioning
confidence: 99%
“…A recent study of 8 weeks of therapy with LDV/SOF found that SVR12 was achieved in 97% of treatment-naïve HCV GT1 patients overall, but the SVR12 rates were lower (93%) in patients with stage 3 ibrosis and in African Americans (83%), warranting some consideration in these speci ic patient populations [5]. Of note, there is also emerging evidence of SVR rates ≥ 95% with the use of 8 weeks of LDV/SOF therapy in GT4 in noncirrhotic treatment-naïve patients; however, this is an offlabel use [6,7].…”
Section: More Informationmentioning
confidence: 99%
“…Treatment regimens are now of shorter duration, less difficult to tolerate, and more effective. [ 8 ] The introduction of these new treatment options can result in greater reduction of prevalence rates. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%